2000
DOI: 10.1054/bjoc.1999.1097
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of oestrogen receptor- α by interleukin-6 in primary cultures of breast cancer epithelial cells

Abstract: Interleukin 6 (IL-6) is secreted by breast tumours and shows synergistic activity with 17β-oestradiol (E2), leading to increases in reductive 17β-hydroxysteroid dehydrogenase activity in breast cancer epithelial cells. However, the mechanisms involved are poorly understood. Using short-term epithelial cultures established from primary breast tumours, we have examined whether IL-6 could directly affect transcriptional activity of oestrogen reception α (ERα). Tumour epithelial cultures were established from 15 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Nevertheless, little is known regarding the direct effects of cytokines on ER expression. IL6 and tumour necrosis factor alpha (TNF-a) are reported to suppress ER expression (Bhat-Nakshatri et al 2004, D'Anello et al 2010, but other studies have presented conflicting results (Speirs et al 2000, Rubio et al 2006. In our hands, IL6 had little effect on ER expression (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Nevertheless, little is known regarding the direct effects of cytokines on ER expression. IL6 and tumour necrosis factor alpha (TNF-a) are reported to suppress ER expression (Bhat-Nakshatri et al 2004, D'Anello et al 2010, but other studies have presented conflicting results (Speirs et al 2000, Rubio et al 2006. In our hands, IL6 had little effect on ER expression (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Although IL-6 expression in early-stage breast carcinomas has been correlated with low grade, oestrogen receptor status and good prognosis (Fontanini et al, 1999;Karczewska et al, 2000), several studies have shown that IL-6 may contribute to disease progression, particularly in advanced breast cancer patients. Indeed, IL-6 can modulate steroid hormone responsiveness by increasing aromatase activity and oestradiol 17 beta-hydroxysteroid dehydrogenase activity in malignant tissue and by activating oestrogen receptor-a (Duncan et al, 1994;Singh et al, 1999;Speirs et al, 2000). IL-6 may promote cell migration by activating the mitogen-dependent protein kinase pathway, and increase chemotherapeutic resistance by inhibiting the activation of proteases involved in apoptosis (Lotem and Sachs, 1997;Badache and Hynes, 2001).…”
Section: Prognostic Value Of Angiogenic Factors In Breast Cancer T Bamentioning
confidence: 99%
“…IL-6 and oncostatin M induce disruption of cell adhesion and increased motility of breast cancer cells (15,16). IL-6 has also been reported to activate the estrogen receptor in breast cancer cells (17).…”
Section: Introductionmentioning
confidence: 99%